Case report: Transapical transcatheter double valve-in-valve replacement of degenerated aortic and mitral bioprosthetic valves with limited radiopaque landmarks - Zhou, Jiawei; Li, Yuehuan; Zhang, Haibo (Frontiers in Cardiovascular Medicine, 2022)
A 67-year-old male patient who had undergone double valve replacement 11 years before presented with severe dyspnea to our department. The bioprosthetic aortic and mitral valves have failed. Because of the high risk of redo surgery. We perform a simultaneous transapical transcatheter valve-in-valve replacement of degenerated aortic and mitral bioprosthetic valves with limited radiopaque landmarks using the second-generation self-expanding J-valve. The post-operative course was stable and the patient was discharged on post-operative day eight.